Pemanfaatan Dan Pengembangan Model Pembelajaran Inovatif Berbasis ICT Pada Pembelajaran Pendidikan Agama Islam - Yoyo Rodiya; Widyo Nugroho; Seipah Kardipah (Universitas Muhammadiyah Ponorogo, 2022)
Utilization and development of innovative learning models based on ICT (Information and Communication Technology) especially in Islamic Religious Education learning is a necessity in today's digital era as a need and demand of an era that is always dynamic and continues to develop from time to time. The purpose of this research is to understand the utilization and development of ICT-based innovative learning models in Islamic Religious Education learning and to understand Islamic views regarding the use and development of these ICT-based learning models. The results of the study show that the utilization and development of ICT-based Islamic Religious Education learning models can be carried out by using and developing own it learning models, learn it, share it, e-learning, blended learning, multimedia, audio visual, video conferencing and so on. In the perspective of Islamic teachings, there is no prohibition on using and developing ICT-based learning models, it is even recommended as long as the technology contains good values, benefits and expediencies for humans and does not contain or support evil, immorality and damage.